Case of Life-Threatening Pneumonia during the Treatment of a Patient with Acute Bacterial Prostatitis - Kyung Kgi Park; Sung Dae Kim; Young-Joo Kim; Jung-Sik Huh (Urogenital Tract Infection)
Acute bacterial prostatitis is an acute urinary tract infection associated with a bladder outlet obstruction or an immunosuppressed state. A 51-year-old man patient visited the hospital with fever, chills, and acute urinary retention that started the day before his visit after consuming a significant amount of alcohol. Conservative treatments, including catheterization for urinary drainage and antibiotics, were performed. On the third day of treatment for acute prostatitis, he complained of dyspnea. The level of oxygen differentiation was reduced significantly, and the tracheal insertion and ventilator were maintained after the radiological examination. The ventilator was discontinued, and the prostate abscess was operated on the eighth day of hospitalization. He was discharged without complications. This paper reports a case of life-threatening pneumonia and a prostate abscess during the treatment of a patient with acute bacterial prostatitis with a review of the relevant literature.